2019
DOI: 10.1089/jwh.2018.7182
|View full text |Cite
|
Sign up to set email alerts
|

Residential Exposure to PM2.5 and Ozone and Progression of Subclinical Atherosclerosis Among Women Transitioning Through Menopause: The Study of Women's Health Across the Nation

Abstract: Objective: This article aims to examine the association between long-term ambient air pollution and progression of subclinical atherosclerosis with 2-year follow-up among midlife women from the Study of Women's Health Across the Nation (SWAN). Materials and Methods: Carotid duplex ultrasonography was performed in participants from a SWAN ancillary study carried out at the Pittsburgh and Chicago sites. Mean and maximum carotid intima-media thickness (CIMT) and plaque burden were assessed throughout the common, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We extracted data for 2,129 participants (age 52-71 years as of 2002) who lived in BMR in 2002 and met the following criteria: (1) participated in follow-up surveys at least twice (2002 and 2007) or three times (2002, 2007, and 2012) (Adar et al, 2013;Duan et al, 2019;Kaufman et al, 2016;Wang et al, 2019;Wilker et al, 2013;Zhang et al, 2021), and (2) lived in Bangkok, Nonthaburi, Samut Prakan, or Pathum Thani during the study period. We excluded 290 participants who died or were lost to follow-up before 2007, or who moved from the study area in 2007.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…We extracted data for 2,129 participants (age 52-71 years as of 2002) who lived in BMR in 2002 and met the following criteria: (1) participated in follow-up surveys at least twice (2002 and 2007) or three times (2002, 2007, and 2012) (Adar et al, 2013;Duan et al, 2019;Kaufman et al, 2016;Wang et al, 2019;Wilker et al, 2013;Zhang et al, 2021), and (2) lived in Bangkok, Nonthaburi, Samut Prakan, or Pathum Thani during the study period. We excluded 290 participants who died or were lost to follow-up before 2007, or who moved from the study area in 2007.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Thus, the highest degree of increase in CIMT (by 15.6%, 95% CI = 5.7-26.6%) was typical for women over 60 years old [ 34 ]. Subsequently, many studies have confirmed the existence of the relation between exposure to PM 2.5 and the increase in the marker of subclinical atherosclerosis - CIMT [ 35 - 39 ]. One of the significant sources of atmospheric air pollution (increased concentration of PM 2.5) is road transport, especially in conditions of heavy traffic.…”
Section: Description Of Pm 25mentioning
confidence: 99%
“…Association between PM and atherosclerotic lesion has been explored by animal models and population-based studies [ 11 , 12 ], but the results were not generally consistent. Long-term exposure to PM was demonstrated as an important risk factor for CIMT in both cross-sectional and longitudinal studies among late midlife women [ 13 ] or women transitioning through menopause [ 14 ], adolescents or young adults [ 15 ], children [ 16 ], general population [ 17 , 18 ] and even HIV-positive adolescents [ 19 ]. But such association was not found in some other studies for either PM 2.5 [ 20 , 21 ] or PM 10 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%